Graphene Oxide Inserted Poly(N-Vinylcarbazole)/Vanadium Oxide Hole Transport Heterojunctions for High-Efficiency Quantum-Dot Light-Emitting Diodes - Park, Young Ran; Choi, Kyoung Soon; Kim, Jong Chan; Seo, Young Soo; Kim, Soo Young; Kim, Yong-Jin; Choi, Won Kook; Jeong, Hu Young; Yang, Woo Seok; Hong, Young Joon (WILEY, 2017)
This study investigates the effect of graphene oxide (GO) interlayer on electrical and electroluminescent (EL) performances of quantum-dot light emitting diodes (QD-LEDs) with poly(N-vinylcarbazole, PVK)/V2O5-x hole transport layers. The control QD-LEDs basically consist of multilayer heterojunctions of hole transport/injection PVK/V2O5-x bilayers, QD light emission layer, and electron transport ZnO nanoparticle layer, all of which are sequentially spin coated on indium-tin-oxide/glass substrates. The QD-LEDs with GO interlayer inserted between PVK and V2O5-x present superior electrical rectification and EL efficiency than those without GO interlayer. The hole-only devices with GO interlayer evidence higher hole conduction capability than those without GO by an order of magnitude. From ultraviolet photoelectron spectroscopy analysis, the hole transport enhancement in PVK/GO/V2O5-x heterojunctions is found to be responsible for reduced height of the highest hole barrier at QD/PVK interface from 1.74 to 0.75 eV by means of downshift of energy levels of PVK. Such energy level variation of PVK is discussed in terms of heterointerfacial orbital hybridization at PVK/V2O5-x, which are validated by diverse spectroscopies. The ability of GO interlayer to shift the PVK energy levels can be exploited for developing high-performance optoelectronics and electronics with hole transport organic/transition metal oxide heterojunctions.
Keywords: ORGANIC SOLAR-CELLS; INDIUM-TIN-OXIDE; INJECTION LAYER; ELECTRONIC-STRUCTURE; LOW-TEMPERATURE; MOLECULAR-ORIENTATION; RAMAN-SPECTROSCOPY; MOLYBDENUM OXIDE; DIRECT REDUCTION; METAL-OXIDES